The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1387/ijdb.15272389
|View full text |Cite
|
Sign up to set email alerts
|

Scale development in fish: a review, with description of sonic hedgehog (shh) expression in the zebrafish (Danio rerio).

Abstract: In the first part of this paper we review current knowledge regarding fish scales, focusing on elasmoid scales, the only type found in two model species, the zebrafish and the medaka. After reviewing the structure of scales and their evolutionary origin, we describe the formation of the squamation pattern. The regularity of this process suggests a pre-patterning of the skin before scale initiation. We then summarise the dynamics of scale development on the basis of morphological observations. In the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
239
3
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(248 citation statements)
references
References 73 publications
(94 reference statements)
5
239
3
1
Order By: Relevance
“…Comparative studies of ontogenetic process require not only embryonic, but also postembryonic staging tables, as several important morphogenetic processes which form characteristic features of each species (for example, internal and external skeletal structures and scale patterns) are known to proceed during postembryonic stages (Arratia et al, 1990, 1991; Cubbage and Mabee, 1996; Schilling and Kimmel, 1997; Van der Heyden and Huyssune, 2000; Van der Heyden et al, 2000; Witten et al, 2001; Yelick and Schilling, 2002; Mabee et al, 2002; Bird and Mabee, 2003; Sire and Huysseune, 2003; Webb and Shirey, 2003; Elizondo et al, 2005; Sire and Akimenko, 2004; Thorsen and Hale, 2005; Patricia et al, 2007; Patterson et al, 2008; Parichy et al, 2009; Kimmel et al, 2010; Budi et al, 2011; Bensimon‐Brito et al, 2012). However, at present there is no widely available postembryonic developmental staging table for goldfish, in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of ontogenetic process require not only embryonic, but also postembryonic staging tables, as several important morphogenetic processes which form characteristic features of each species (for example, internal and external skeletal structures and scale patterns) are known to proceed during postembryonic stages (Arratia et al, 1990, 1991; Cubbage and Mabee, 1996; Schilling and Kimmel, 1997; Van der Heyden and Huyssune, 2000; Van der Heyden et al, 2000; Witten et al, 2001; Yelick and Schilling, 2002; Mabee et al, 2002; Bird and Mabee, 2003; Sire and Huysseune, 2003; Webb and Shirey, 2003; Elizondo et al, 2005; Sire and Akimenko, 2004; Thorsen and Hale, 2005; Patricia et al, 2007; Patterson et al, 2008; Parichy et al, 2009; Kimmel et al, 2010; Budi et al, 2011; Bensimon‐Brito et al, 2012). However, at present there is no widely available postembryonic developmental staging table for goldfish, in practice.…”
Section: Introductionmentioning
confidence: 99%
“…apoeb transcripts were subsequently restricted to the posterior margin epidermis of the papilla (Monnot et al, 1999), a pattern also observed with esr2a (Fig. 4G,M) and sonic hedgehog (shh; Sire and Akimenko, 2004). Ultrastructural studies suggested that epidermal-dermal interactions continued to occur in the posterior region of the formed scale (Sire et al, 1997a).…”
Section: During the Larval-juvenile Transition And In Adultsmentioning
confidence: 57%
“…In zebrafish, the first scales appear on the lateral and posterior part of the fish at the midregion of the caudal fin and squamation then spread forward, downward, and laterally (Waterman, 1970;Sire et al, 1997a;Sire and Akimenko, 2004). Starting from a homogeneous rbp4 expressed epidermal cover (Fig.…”
Section: During the Larval-juvenile Transition And In Adultsmentioning
confidence: 99%
See 2 more Smart Citations